Precisely modulated 2D PdCu alloy nanodendrites as highly active peroxidase mimics for the elimination of biofilms. (2nd November 2022) - Yuan, Guotao; Zhang, Shitong; Yang, Zaixing; Wu, Shunjie; Chen, Huanjun; Tian, Xin; Cheng, Si; Pan, Yue; Zhou, Ruhong
Abstract : 2D PdCu alloy nanodendrites manifest effective peroxidase-like activity and striking biofilm inhibition properties. Abstract : Pd-based nanomaterials are good candidates for antibacterial applications because of their high catalytic activity and good biocompatibility. Nonetheless, there is still much work to do to improve the catalytic activity of Pd nanomaterials as antibacterial agents, particularly for anti-biofilms. In this work, Cu was introduced into Pd to form a series of 2D PdCu alloy nanodendrites (PdCu NDs) as high-performance peroxidase mimics based on flexible control of compositions. Remarkably, catalytic kinetics show that the composition-dependent synergy in the PdCu NDs strongly enhances the peroxidase-like activity. The detailed theoretical study reveals that the tuning of the electrostatic adsorption and dissociative chemisorption of the H2 O2 molecule on PdCu ND surfaces by the precise introduction of Cu plays a key role in obtaining superior peroxidase-like catalytic activity. Significantly, the distinct peroxidase-like properties of the fine-tuned PdCu NDs endow them with excellent biofilm elimination capability via the generation of hydroxyl radicals. This work offers a great opportunity to design noble metal nanozymes with enhanced performance, which might advance the development of nanozymes as a new class of highly efficient antibacterial agents.